Distributed File Sharing and Retrieval Model for Cloud Virtual Environment - Ali, M.; Soomro, N. Q.; Ali, H.; Awan, A.; Kirmani, M. (Engineering, Technology & Applied Science Research, 2019)
Cloud-based storage services are multiplying and are being adapted mostly for data storage. At the same time, many potential problems pertaining to data storage and security are being addressed. This research provides the architecture for splitting user data and the solution in retrieving different data chunks, stored on different cloud storages. By doing this, not only the load on a single server is reduced but security and storage are efficiently used. Data would be stored and retrieved in slices, hence the chances of data forgery are diminishing. File processing will be faster as split parts would be fetched from different clouds, enabling parallel processing.